Developing adaptive resilience in infrastructure systems: an approach to quantify long-term benefits. (30th January 2023) - Singh, Prerna; Amekudzi-Kennedy, Adjo; Ashuri, Baabak; Chester, Mikhail; Labi, Samuel; Wall, Thomas A.
ABSTRACT: To enable systems to adapt to changing future conditions, ensuring adaptive capacity in resilience planning is critical. This paper presents an approach to evaluate the long-term benefits of adaptive resilience in infrastructure systems under future uncertainty. The methodology uses long timeframe assessment methods based on NPV and approaches to quantifying different levels of uncertainty along with multi-criteria assessment methods. The approach is demonstrated using three case studies, where investments have focused on different aspects of adaptive resilience in various infrastructure systems. The results demonstrate the increasing benefits of adaptive strategies over time with ongoing learning and the evolving nature of resilience needs. The presented approach can be used by decision-makers in multiple infrastructure sectors. A flexible approach to evaluate the long-term benefits of building adaptive capacity to enhance resilience, this methodology can be a useful tool for practitioners and policymakers to present a business case for long-term adaptive resilience investments..